2010
DOI: 10.1111/j.1742-4658.2010.07776.x
|View full text |Cite
|
Sign up to set email alerts
|

High diversity of polyketide synthase genes and the melanin biosynthesis gene cluster in Penicillium marneffei

Abstract: Despite the unique phenotypic properties and clinical importance of Penicillium marneffei, the polyketide synthase genes in its genome have never been characterized. Twenty‐three putative polyketide synthase genes and two putative polyketide synthase nonribosomal peptide‐synthase hybrid genes were identified in the P. marneffei genome, a diversity much higher than found in other pathogenic thermal dimorphic fungi, such as Histoplasma capsulatum (one polyketide synthase gene) and Coccidioides immitis (10 polyke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
108
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 103 publications
(111 citation statements)
references
References 26 publications
2
108
0
1
Order By: Relevance
“…Six genes related to the biosynthesis of DHN-melanin were clustered together (60,61) and genetically regulated by the expression of brlA (64). Our previous study revealed the existence of this gene cluster in P. marneffei (22). RNA-seq data from this study showed that all six genes in the cluster are significantly downregulated at 37°C (Fig.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Six genes related to the biosynthesis of DHN-melanin were clustered together (60,61) and genetically regulated by the expression of brlA (64). Our previous study revealed the existence of this gene cluster in P. marneffei (22). RNA-seq data from this study showed that all six genes in the cluster are significantly downregulated at 37°C (Fig.…”
Section: Resultsmentioning
confidence: 96%
“…Only in the past decade have studies focused on the molecular mechanisms of phase transition with the application of novel genetic approaches in P. marneffei (20)(21)(22). To date, more than 40 P. marneffei genes have been cloned or experimentally characterized (23)(24)(25)(26)(27).…”
Section: P Marneffei Blastomyces Dermatitidis Histoplasma Capsulatmentioning
confidence: 99%
“…The THN skeleton is synthesized by multidomain nonreducing iterative polyketide synthases (NR-PKSs). In some cases, melanin genes are clustered at one genetic locus, but they can also be dispersed throughout the genome (Woo, et al, 2010). Although nonessential, melanin pigments are important for survival and longevity.…”
Section: Introductionmentioning
confidence: 99%
“…Genes encoding Mp1p homologues were identified and used for construction of a highly discriminative multilocus sequence typing scheme for P. marneffei (9). Twenty-three putative polyketide synthase (PKS) genes and two putative PKS-nonribosomal peptide synthase hybrid genes were identified, a diversity much higher than those of other pathogenic thermal dimorphic fungi, such as Histoplasma capsulatum (one PKS gene) and Coccidioides immitis (10 PKS genes) (11). Further in-depth analysis would uncover additional clues that explain the virulent and thermal dimorphic behaviors of this unique Penicillium species.…”
mentioning
confidence: 99%